Huangqin Tang Interference With Colitis Associated Colorectal Cancer Through Regulation of Epithelial Mesenchymal Transition and Cell Cycle - Ma, Xuran; Wang, Dunfang; Feng, Xue; Liu, Yaqing; Li, Jia; Yang, Weipeng (Frontiers in Pharmacology, 2022)
Background Although the exact molecular mechanisms of colitis associated colorectal cancer are not fully understood, the chronic inflammation positively correlated with tumorigenesis. The Traditional Chinese Medicine herbal formulation Huangqin Tang has significant anti-inflammatory effects. We investigated whether HQT can ameliorate the progression of inflammation to cancer through its anti-inflammatory effects by using relevant predictions and experiments. Methods: We used Azoxymethane/Dextran Sodium Sulfate method to induced mice colitis associated colorectal cancer model. After preventive administration of Huangqin Tang to model mice, colonic tissues were taken for quantitative proteomic analysis of Tandem Mass Tags, the proteomic results were then experimentally validated using molecular biology approach. Results: Proteomic screening revealed that the effect mechanism of Huangqin Tang on colitis associated colorectal cancer model mice may be related to infinite replication which demonstrated abnormal G1/S checkpoint and epithelial mesenchymal transition acceleration. The levels of inflammatory factors Interleukin-1α, Interleukin-1β, Interleukin-6, Tumor necrosis factor-α were significantly reduced in colitis associated colorectal cancer mice treated with Huangqin Tang；the aberrant expression of G1/S checkpoint associated sites of cell cycle protein-dependent kinase 4, Cyclin D1 and dysregulation of related sites of the WNT pathway which are most related to the acceleration of epithelial mesenchymal transition process including WNT3A, β-catenin, E-cadherin, Gsk3β have been improved. Conclusion: Reducing inflammation and thus inhibiting the progression of colitis associated colorectal cancer by using Huangqin Tang is effective, and the mechanism of action may be related to the inhibition of uncontrolled proliferation during tumorigenesis. In the follow-up, we will conduct a more in-depth study on the relevant mechanism of action.